2011
DOI: 10.1021/ol200231z
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular Cyclization of in Situ Generated Adducts Formed between Thioamide Dianions and Thioformamides Leading to Generation of 5-Amino-2-thiazolines and 5-Aminothiazoles, and Their Fluorescence Properties

Abstract: Reactions of thioamide dianions, derived from secondary N-arylmethyl thioamides using BuLi, with thioformamides followed by the addition of iodine to yield 5-amino-2-thiazolines are described. Treatment of the 5-amino-2-thiazolines with iodine leads to a highly efficient production of 5-aminothiazoles. When N,N-diarylthioformamides are employed in this process, fluorescent 5-N,N-diarylthiazoles are obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…The 3026,3005,1591,1548,1491,1448,1410,1266,1236,1213,1032,1002,992,963,831,753,728,694 8,121.6,121.9,123.4,124.0,126.2,127.4,128.1,128.8,129.3,129.4,139.2,140.4,145.4,150.3,166.8;MS (EI) According to the general procedure for thiazolines, compound 8 was prepared. The crude material was purified by column chromatography (SiO 2 , hexane:EtOAc = 15:1) to give 8 (0.87 g, 60%) as a brown liquid: IR (KBr) 3059, 3029, 2956, 2926, 1686, 1597, 1491, 1450, 1276, 1241, 1034, 948, 908, 846, 751, 728, 696 cm -1 ; 1 H NMR (400 MHz,…”
Section: General Procedures For the Preparation Of Thiazolines To A Smentioning
confidence: 99%
“…The 3026,3005,1591,1548,1491,1448,1410,1266,1236,1213,1032,1002,992,963,831,753,728,694 8,121.6,121.9,123.4,124.0,126.2,127.4,128.1,128.8,129.3,129.4,139.2,140.4,145.4,150.3,166.8;MS (EI) According to the general procedure for thiazolines, compound 8 was prepared. The crude material was purified by column chromatography (SiO 2 , hexane:EtOAc = 15:1) to give 8 (0.87 g, 60%) as a brown liquid: IR (KBr) 3059, 3029, 2956, 2926, 1686, 1597, 1491, 1450, 1276, 1241, 1034, 948, 908, 846, 751, 728, 696 cm -1 ; 1 H NMR (400 MHz,…”
Section: General Procedures For the Preparation Of Thiazolines To A Smentioning
confidence: 99%
“…; H, 0.95 Å and S, 1.85 Å)[82][83][84][85][86][87]. Thus suggesting the existence of non-conventional CeH⋯N and CeH⋯S intramolecular hydrogen bonds[88], similar to those found in most 2-phenylthiazole derivatives[82][83][84][85][86][89][90][91][92].…”
mentioning
confidence: 85%
“…We have previously reported that the fluorescence properties of 5‐ N ‐arylaminothiazole 1 (Scheme ) can be controlled by the substituents, and that the presence of electron‐donating groups on the nitrogen atom at the 5‐position bathochromically shifts the emission . 5‐Aminothiazole 1 contains monocyclic homo‐ and heteroaromatic groups, whereby their conformation is intricately correlated to both solvent and temperature.…”
Section: Methodsmentioning
confidence: 99%